NUTRITION EDUCATION IN TARAKANITA ELEMENTARY SCHOOLIN MAGELANG AND ITS EFFECTS ON THE CHANGES IN KNOWLEDGE, BEHAVIOR, AND ATTITUDE - Suhartatik, Nanik; Handayani, Sri; Ningrum, Kirana Swasti; Mustofa, Akhmad; Wulandari, Yustina Wuri (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Wrong eating behavior in school-age children may end up in serious nutrition problems. During the periods of growth of elementary-school-age children, attention should be paid to their nutrition fulfilment. Inadequate knowledge of nutrition education may lead them to unhealthy food consumption. Healthy food itself is one which contains balanced nutritions. The introduction of fast food into the food health sector in Indonesia can also influence public diets. In order to evade future nutrition problems, nutrition education is thus necessary for elementary-school-age children, especially for the purpose of enhancing knowledge, attitude, and selection practice healthy foods and snacks. The menus for school-age children must have nutrition contents which are balanced and needed by the body. This research determines the effect of nutrition education on SD Tarakanita Magelang fifth graders’ knowledge of healthy and nutritious food consumption. The 64 respondents enrolled in this research were divided into two classes: education and non-education classes. The respondents consisted of 10–13-year-old fifth graders. This research used a questionnaire for data collection. Pre-test was first conducted to both education and non-education classes. Then, to the education class four nutrition education materials were delivered. Two months afterward the final data were derived through post-test. The research results showed that the provision of nutrition education for the fifth graders of SD Tarakanita Magelang affected their food consumption knowledge, attitudes, and behaviors. Keywords: elementary school, nutrition education, behavior, attitude